Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Oral administration of dopamine boosts anti-Vibrio immunity in shrimp through Dorsal pathway activation - Zi-ang Wang; Shun Liu; Zexu Zhao; Xiaojia Liao; Linwei Yang; Hongliang Zuo; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2026)

Virus-inclusive microbial network relationships align with the stress gradient hypothesis in saline-alkali agroecosystems - Fang Li; Linwei Wu; Changlin Xu; Shuwen Guo; Jinhua Zhao; Yi Wang; Peipei Li; Biao Zhu (Soil Biology and Biochemistry, 2026)

Heteroaptamer recognition mediated strand displacement amplification for efficient electrochemical analysis of beta-2-microglobulin in breast milk - Yaqin Tang; Tingting He; Linwei Pan; Yanni Wang; Xiaolong Li; Xia Zhao; Daxiu Li; Baoting Dou (Food Chemistry, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

Effect of ultrasonication on the structure and stability of protein modified liposomes - Linwei Zhao; Libin Sun; Weining Wang; Mingzhe Pan; Lanxia Qin; Dianyu Yu (Food Hydrocolloids, 2026)

The unwetted height of transom-stern monohull ships and the Neumann–Michell ship flow computations - Chao Ma; Haolin Yang; Linwei Wang; Yingjiang Zhao; Jie Gong; Zhenlong Fang (Ocean Engineering, 2025)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Multiple surge trigger mechanisms of compound glacier: a case study on recent surges of Aru-4 Glacier, Western Tibetan Plateau - Weijin Guan; Bo Cao; Linwei Sha; Baotian Pan; Xuanru Zhao; Zongli Jiang; Guangjian Wu (Journal of Mountain Science, 2025)
Surge-type glaciers are widely developed in mountainous areas around the world. Understanding the trigger mechanism of glacier surge is a prerequisite for addressing their impacts on hydrological assessments, disentangling climate-glacier linkages, and mitigating downstream hazards. Most glacier surges occur in the compound glaciers; however, attention paid to the trigger mechanisms of such surges is minimal. This study confirmed two surges in the northern and southern branches of the Aru-4 glacier, respectively, in the Western Tibetan Plateau, using multisource remote sensing data. The northern branch of the Aru-4 glacier entered the active phase in 1999 and the active phase lasted for 6 years. The southern branch of the Aru-4 glacier entered the active phase in 2007 and the active phase lasted for 9 years. The southern branch of the Aru-4 glacier experienced a long period of retreat before the northern branch surged and their tongues were in a detached state. The northern branch surge carried a large amount of ice to the frontal area, blocking the downward transport of ice from the southern branch and initiated surge. Through the analysis of two surge processes of Aru-4 glacier, we found a new surge mechanism for compound glaciers. It was revealed that surges in such glaciers are not only triggered by the reduction in basal sliding resistance caused by the internal factors. These surges initiated in the upper part of the glacier then propagated to down glacier by intense compression force. Furthermore, surges can also be triggered by external intervention of blocking by other branches. This external trigger initiates the surge in the lower part of the glacier then propagated to the upper part by longitudinal traction force. In addition, comparing with the surge triggered by the internal factors, the surge triggered by the external intervention may have a more dramatic process.

From Kelvin Wave Patterns to Ship Displacement: An Inverse Prediction Framework Based on a Hull Form Database - Chao Ma; Linwei Wang; Yingjiang Zhao; Haolin Yang; Haoqing Huang; Bohan Cao (Journal of Marine Science and Engineering, 2025)
The estimation of a ship’s displacement volume, ∇, from remote sensing data is of considerable practical value for maritime surveillance and vessel characterization. This paper introduces a practical framework for the inverse estimation of displacement volume from Kelvin ship waves, building upon a prior study through two key extensions. First, the wave amplitude function is recovered using Fourier series expansions combined with the stationary phase method. The displacement volume is then estimated via a two-step procedure: an initial estimate is obtained by identifying a hull with similar amplitude characteristics from a database, followed by a refinement that incorporates discrepancies between the target and candidate wave amplitude functions. In the case studied, the proposed approach achieves a prediction error of 4.02%, demonstrating its potential for non-invasive extraction of hull information from remote sensing data.

Resveratrol-integrated Se-chitosan nanogel for protein corona-mediated blood-brain barrier traversing and anti-inflammatory treatment for Parkinson's disease - Yuan Cao; Linwei Zhao; Qing Li; Bo Song; Yuming Xu; Lin Jiang; Shaohua Li (Chemical Engineering Journal, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Combined multispectral analysis and molecular docking to research the interaction of soybean isolate protein with different kinds of phospholipid liposomes and its effect on liposome properties - Linwei Zhao; Chunlei Liu; Tong Wang; Libin Sun; Fei Wu; Dianyu Yu (Food Chemistry, 2025)

DRAM2 inhibits white spot syndrome virus infection via activating autophagy in Penaeus vannamei - Xiyu Huang; Mingming Zhao; Jieyu Huang; Mingjian Liu; Linwei Yang; Chuanqi Wang (Fish & Shellfish Immunology, 2025)

Establishment of virus-induced gene silencing in Euphorbia lathyris L. and its application in casbene synthase (CBS) gene functional analysis - Wei Lyu; Mei Tian; Long Huang; Bi Wang; Pirui Li; Wanli Zhao; Linwei Li; Xu Feng; Shu Xu; Yu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Electroformation and characterization of soybean protein isolate hydrolysates-modified liposomes - Libin Sun; Linwei Zhao; Zhe Huang; Fei Wu; Mingzhe Pan; Dianyu Yu (Food Hydrocolloids, 2025)

The Distribution Characteristics and Influencing Factors of the CO2 Fluxes Across the Sea–Air Interface in the Artificial Reefs Area of Sanheng Island - Mingdong Zhu; Kai Wang; Xu Zhao; Linwei Dai; Lei Chen; Hanyu Zhou (Journal of Marine Science and Engineering, 2024)
In order to study the impact of artificial reef construction on marine carbon sinks, a one-year monitoring and analysis were carried out in the Sanheng artificial reef areas of Shengsi Island. The main parameters observed were sea surface temperature, salinity, pH, total alkalinity (TA), and dissolved inorganic carbon (DIC). The partial pressure of CO2 (pCO2w) in the surface water and the CO2 flux (FCO2) across the sea–air interface were calculated and analyzed. The results showed that the annual range of surface water pCO2w was 34.48~501.53 μatm, and the partial pressure of CO2 decreases in the following order: winter, spring, autumn, summer. The FCO2 was significantly negatively correlated with temperature and significantly positively correlated with salinity and TA. The FCO2 in the four seasons decreases in the following order: winter, spring, autumn, summer. The annual sea–air flux in the survey area ranged from −108.79 to 41.74 mmol m−2 d−1. In winter, both the reef area and the control area displayed positive FCO2 values, indicating a source of CO2, while in the other three seasons, CO2 flux values were negative, indicating an overall CO2 sink. Additionally, in autumn, the reef area exhibited a stronger CO2 sink than the control area. The results indicated that the construction of artificial reefs has a certain carbon sink effect, with no significant difference in effectiveness between different artificial reef construction models.

A novel perlucin with immune regulatory functions protects Litopenaeus vannamei against Vibrio parahaemolyticus infection - Zi-ang Wang; Linwei Yang; Zexu Zhao; Shaoping Weng; Jianguo He; Xiaopeng Xu (Fish & Shellfish Immunology, 2024)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Complex phospholipid liposomes co-encapsulated of proanthocyanidins and α-tocopherol: Stability, antioxidant activity and in vitro digestion simulation - Linwei Zhao; Donghua Wang; Jiaye Yu; Xu Wang; Tong Wang; Dianyu Yu; Walid Elfalleh (Food Bioscience, 2024)

Understanding the metabolism and scaling law in construction projects: Evidence from China - Xiaowei Zou; Shuhui Tan; Jingke Hong; Linwei Du; Qingyue Zhao; Jian Zuo (Environmental Impact Assessment Review, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Macro and micro connections for slip zone soils of landslide under wetting–drying cycles in the Three Gorges Reservoir area - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Yanming Ding; Jiajia Meng (Landslides, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Landslide susceptibility mapping in Three Gorges Reservoir area based on GIS and boosting decision tree model - Fasheng Miao; Fancheng Zhao; Yiping Wu; Linwei Li; Ákos Török (Stochastic Environmental Research and Risk Assessment, 2023)

Clinical Features and Skin Microbiome of Tinea Scrotum: An Observational Study of 113 Cases in China - Zixiang Si; Juan Bai; Linwei Wei; Honglei Zhao; Songting Wang; Bin Liu; Jingjing Xu; Hong Fang; Zongxin Ling; Jianjun Qiao (Mycopathologia, 2023)

Mapping conduits in two-dimensional heterogeneous karst aquifers using hydraulic tomography - Xintong Wang; Xiang-Zhao Kong; Linwei Hu; Zhenhao Xu (Journal of Hydrology, 2023)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Dissimilar responses of fungal and bacterial communities to soil transplantation simulating abrupt climate changes - Mengxin Zhao; Bo Sun; Linwei Wu; Feng Wang; Chongqing Wen; Mengmeng Wang; Yuting Liang; Lauren Hale; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2019)
Both fungi and bacteria play essential roles in regulating soil carbon cycling. To predict future carbon stability, it is imperative to understand their responses to environmental changes, which is subject to large uncertainty. As current global warming is causing range shifts toward higher latitudes, we conducted three reciprocal soil transplantation experiments over large transects in 2005 to simulate abrupt climate changes. Six years after soil transplantation, fungal biomass of transplanted soils showed a general pattern of changes from donor sites to destination, which were more obvious in bare fallow soils than in maize cropped soils. Strikingly, fungal community compositions were clustered by sites, demonstrating that fungi of transplanted soils acclimatized to the destination environment. Several fungal taxa displayed sharp changes in relative abundance, including Podospora , Chaetomium , Mortierella and Phialemonium . In contrast, bacterial communities remained largely unchanged. Consistent with the important role of fungi in affecting soil carbon cycling, 8.1%–10.0% of fungal genes encoding carbon‐decomposing enzymes were significantly ( p

A comparison of next-generation sequencing with clone sequencing in the diet analysis of Asian great bustard - Minghao Gong; Yu Ning; Morigen Han; Chenyang Zhao; Jingxing Tian; Linwei Li; Hongye Xiao; Gang Liu (Conservation Genetics Resources, 2019)

Ionizing radiation exposure: hazards, prevention, and biomarker screening - Hongxiang Mu; Jing Sun; Linwei Li; Jie Yin; Nan Hu; Weichao Zhao; Dexin Ding; Lan Yi (Environmental Science and Pollution Research, 2018)